2016
DOI: 10.1039/c5cc10217k
|View full text |Cite
|
Sign up to set email alerts
|

Addition of silylated nucleophiles to α-oxoketenes

Abstract: A general evaluation of silylated nucleophiles to intercept transient α-oxoketenes generated by microwave-assisted Wolff rearrangement of 2-diazo-1,3-dicarbonyl compounds is presented. Original scaffolds and synthetic intermediates are accessed in a rapid, efficient and easy-to-handle way. Mechanistic studies by DFT calculations and some post-functionalizations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This could be evidenced in the case of 4b , the prolonged exposure to air of which resulted in the formation of 4‐bromo‐benzoic acid and furan‐3‐one 2b (Scheme ). Notably, product 2b was previously obtained by a (4 + 1) annulation between the α‐oxoketene derived from diazodimedone and trimethylsilyldiazomethane (Scheme b) …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This could be evidenced in the case of 4b , the prolonged exposure to air of which resulted in the formation of 4‐bromo‐benzoic acid and furan‐3‐one 2b (Scheme ). Notably, product 2b was previously obtained by a (4 + 1) annulation between the α‐oxoketene derived from diazodimedone and trimethylsilyldiazomethane (Scheme b) …”
Section: Resultsmentioning
confidence: 91%
“…[4] Using this technique, we have recently examined their reactions with stabilized phosphorous ylides that triggered either standard or abnormal Wittig olefinations of the α-oxoketenes [5] and with trimethylsilyldiazomethane-a nitrogen ylide-that afforded a few furan-3-ones 2 by (4 + 1) annulations followed by hydrolysis (Scheme 1). [6] However, the synthetic value of the latter transformation was limited because it was not possible to introduce efficiently a substituent or a functional group on the one-carbon atom nitrogen ylide cycloaddition partner, for example using ethyl diazoacetate. This prompted us to investigate the reactivity of stable sulfur ylides 3 with α-oxoketenes in order to prepare 3-hydroxyfurans of type 4 through a related (4 + 1) annulation reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Using this approach, the chemistry of these electrophilic reactive intermediates has been revisited, including their reactions with heteroatom-based, [8] carbon-based, [9] and silylated nucleophiles, [10] N,N-bis-nucleophiles, [11] imines, [12] 1,3-dipoles, [13] and aza-dienes. [7] Using this approach, the chemistry of these electrophilic reactive intermediates has been revisited, including their reactions with heteroatom-based, [8] carbon-based, [9] and silylated nucleophiles, [10] N,N-bis-nucleophiles, [11] imines, [12] 1,3-dipoles, [13] and aza-dienes.…”
Section: Resultsmentioning
confidence: 99%
“…A few years ago we reported on the microwave-assisted thermal Wolff rearrangement of 2-diazo-1,3-dicarbonyl compounds as an extremely convenient source of α-oxoketenes. [7] Using this approach, the chemistry of these electrophilic reactive intermediates has been revisited, including their reactions with heteroatom-based, [8] carbon-based, [9] and silylated nucleophiles, [10] N,N-bis-nucleophiles, [11] imines, [12] 1,3-dipoles, [13] and aza-dienes. [14] Notably, it was found that electron-rich heterocycles could undergo a Friedel-Crafts-type α-ketoacylation with α-oxoketenes to give the corresponding 1,3-diketones, [9] and that properly functionalized electron-rich heterocycles could undergo cascade reactions initiated by a Friedel-Crafts α-ketoacylation elemental step.…”
Section: Resultsmentioning
confidence: 99%